Recognizing Adat Law: Problems and Challenges in Modern Law System in Indonesia - Ikhda Fitria (The Indonesian Journal of International Clinical Legal Education, 2020)
Adat law is a law that was born purely from the life of the Indonesian people, this law was born before Indonesia itself was born, regulated the lives of a group of individuals who are members of the community, and passed down from generation to generation. Its unwritten nature does not diminish its existence in the realm of Indonesian law, it is still respected and adhered by people called adat peoples, and its sanctions that are different from ordinary law also make this law unique. Its existence on Indonesian is also supported by the existence of a legal basis that strengthens its existence. This is adat law, a law that is considered as a law that greatly reflects Indonesian community.